Is salivary IgA level a potential biomarker for immunosuppression in HIV‐positive children? A systematic review and meta‐analysis. (1st June 2017) - Javed, Fawad; Akram, Zohaib; Binshabaib, Munerah Saleh; ALHarthi, Shatha Subhi; Kellesarian, Sergio Varela; Vohra, Fahim
Summary: The aim of this systematic review was to determine whether or not assessment of salivary secretory immunoglobulin A (sIgA) levels could be a potential biomarker for immunosuppression in HIV‐positive children. The Patient, Exposure, Comparative, Outcome question was "Is sIgA level a potential biomarker for immunosuppression in HIV‐positive children?" Electronic and manual literature searches were conducted in indexed databases (MEDLINE, PubMed, EMBASE, ScienceDirect, and SCOPUS databases) up to and including June 2017. The primary outcome was total mean salivary levels of IgA among HIV seropositive and seronegative children (controls). The weighted mean differences (WMD) of outcomes and 95% confidence intervals (CI) for total mean salivary IgA levels were calculated using a random effect model. Six studies were included. Three studies showed significantly lower salivary IgA levels in HIV‐infected children compared with controls. Two studies showed comparable IgA levels in HIV infected and controls. One study showed significantly higher levels of salivary IgA in HIV‐infected children as compared to controls. Considering the total mean salivary IgA levels among HIV seropositive and seronegative children, a high degree of heterogeneity (Q value = 254.09, P < .0001, I 2 = 98.82%) was noticed among both groups. The overall WMD was not significant (WMD = −1.18, 95% CI, −1.91 to −0.44, P = .39). Whether salivary IgA level is a potential biomarker for immunosuppression in HIV‐positive children remains debatable because of limited information available in the current literature. Further, high‐quality case‐control studies with larger sample size and more solid methodological aspects are required.